Language and the Moving Body: Directive Actions With the Finnish kato “look” in Nature-Related Activities - Siitonen, Pauliina; Rauniomaa, Mirka; Keisanen, Tiina (Frontiers in Psychology, 2021)
The article explores how social interaction is accomplished through intertwined verbal and bodily conduct, focusing on directive actions that include a second-person imperative form of the Finnish verb katsoa ‘to look’, typically kato. The study draws on video recordings of various outdoor activities in nature, mostly from family interaction with small children, and employs interactional linguistics and conversation analysis as its analytic framework. The directive kato actions in focus are produced 1) as noticings, to initiate a new course of action by directing the recipient to look at and possibly talk about a target that the speaker treats as newsworthy; 2) as showings, to initiate an evaluative course of action by directing the recipient to look at and align with the speaker’s stance toward the target; or 3) as prompts, to contribute to an ongoing course of action by directing the recipient to do something relevant to or with the target. Apart from the use of kato, the actions differ in their design. In noticings, the target is typically named verbally and pointed at through embodied means, but the participants remain at some distance from it (e.g. kato muurahaispesä tuossa ‘look an anthill there’). In showings, the participant producing the action typically approaches the recipient with the target in hand so that the naming of the target is not necessary but, by evaluating the target themselves, the shower explicates how the target should be seen (e.g. kato kuinka jättejä ‘look how giant {ones}’). In prompts, neither the target nor the intended action are named, but the target is typically indicated by embodied means, for example, by the participants' approaching and pointing at it, and the intended action is inferable from the participants’ prior conduct (e.g. kato tuossa ‘look there’ and pointing at a berry in the participants’ vicinity when berry picking has been established as relevant). By examining these three grammar-body assemblages, the article uncovers regularities in the co-occurrence of multiple modalities and contributes to new understandings of language use in its natural ecology – in co-present social interaction.